Amorphous NiCoMoxMny heterojunction electrode material doped with crystalline Ag and preparation method of amorphous NiCoMoxMny heterojunction electrode material
By mixing crystal AG in amorphous NicomoxMny, heterogeneous knot electrode materials are formed, and a one -step water thermal method is used to solve the problem of complex preparation of the existing composite materials. The effect of long cycle life is suitable for large -scale production.
Patent Information
- Application Number
- CN202411801736.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when amorphous materials are combined with crystalline materials, the preparation process is relatively complicated and is not suitable for large-scale production.
By doping crystal AG to amorphous Nicomoxmny, heterogeneous electrode materials are formed, and a one -step water heating method is used to simplify the process.
It improves the guidance and electrochemical properties, prolongs the cycle life, and makes materials apply to large -scale production.
Smart Images

Figure CN119361333A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of supercapacitors, and in particular to an amorphous NiCoMo doped with crystalline Ag. x Mn y Heterojunction electrode material and preparation method. Background Art
[0002] In recent years, with the intensification of energy crisis and environmental degradation, the demand for new clean renewable energy and energy storage devices with excellent performance has been increasing day by day. Supercapacitors have attracted widespread attention due to their fast charging and discharging speed, long cycle life, low cost, easy maintenance, and low working environment requirements. Supercapacitors are mainly composed of electrode materials, diaphragms, current collectors, electrolytes, and external packaging materials. Among them, electrode materials are the key factors affecting the performance of supercapacitors.
[0003] At present, most of the electrode materials that are of major concern are crystalline electrode materials. Crystalline electrode materials have high electrical conductivity, but due to the insertion and extraction of ions during the cycle, the crystalline electrode materials are easily pulverized, affecting their cycle stability. Compared with crystalline electrode materials, amorphous electrode materials have the following advantages: longer cycle life, more active sites, and faster ion transport channels. Based on the above advantages, amorphous electrode materials have better electrochemical properties. However, the low electrical conductivity of amorphous electrode materials restricts the application of materials.
[0004] Considering the low conductivity characteristics of amorphous electrode materials, compounding amorphous materials with high conductivity materials helps to improve their electrochemical performance. For example, compounding amorphous materials with carbon materials, and compounding amorphous materials with crystalline materials. Among them, the composite of amorphous materials and crystalline materials not only has the characteristics of high conductivity of crystalline materials, but also has the characteristics of long cycle life of amorphous materials, and the composite of the two provides more active sites, thereby improving electrochemical performance. For example, the patent with application number CN202311391799.7 discloses a nickel oxalate composite amorphous nickel cobalt boride supercapacitor electrode material and preparation method and application, nickel oxalate is generated by a hydrothermal method, and then nickel oxalate is compounded with amorphous nickel cobalt boride by a liquid phase method. Due to the synergistic effect of nickel oxalate and amorphous nickel cobalt boride, the structural damage caused by the redox process during charging and discharging is slowed down, and the stability and specific capacity of the material are improved. The patent with application number CN202010376302.4 discloses a method for preparing a crystalline molybdenum oxide-amorphous nickel disulfide (MoO3@Ni3S2) material for supercapacitors. First, crystalline Ni3S2 nanosheets are generated in situ on the surface of nickel foam by a hydrothermal method, and then amorphous MoO3 is further synthesized on the crystalline Ni3S2 nanosheets by solvent heat to obtain a crystalline-amorphous MoO3@Ni3S2 material. The crystalline Ni3S2 nanosheet array is arranged on the surface of nickel foam, and the amorphous MoO3 is intercalated between the crystalline Ni3S2 nanosheets. On the one hand, this patent inherits the high conductivity of crystalline Ni3S2, and on the other hand, the amorphous structure of amorphous MoO3 can accelerate the transfer of charge, thereby promoting the electrochemical reaction and achieving high specific capacitance. However, the above two patents are not suitable for large-scale production due to the complicated sample preparation process. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides an amorphous NiCoMo doped with crystalline Ag. x Mn y A heterojunction electrode material and a preparation method are provided to solve the problem that the preparation process is relatively complicated and not suitable for large-scale production when amorphous materials and crystalline materials are currently combined; the electrode material obtained by the present invention maintains relatively high electrical conductivity, relatively high electrochemical performance and long cycle life.
[0006] The present invention is achieved through the following technical solutions: Amorphous NiCoMo doped with crystalline Ag x Mn y Heterojunction electrode materials can improve amorphous NiCoMo x Mn y The specific capacity and cycle life of the heterojunction electrode material are composed of amorphous NiCoMo xMn y and crystalline Ag, wherein crystalline Ag is doped in amorphous NiCoMo x Mn y In the amorphous NiCoMo x Mn y The x and y in the equation satisfy the following formula: 0<x≤1, 0≤y<1, x+y=1.
[0007] Amorphous NiCoMo doped with crystalline Ag x Mn y A method for preparing a heterojunction electrode material comprises the following steps: S1, when y=0, uniformly mixing the nickel foam with a first mixed solution containing a cobalt salt, ammonium molybdate and a silver salt, wherein the molar ratio of the cobalt salt, the ammonium molybdate and the silver salt is (4.9-7.35):0.7:(0.5-1.5), to obtain a first mixed system; When 0<y<1, the nickel foam is evenly mixed with a second mixed solution containing a cobalt salt, a manganese salt, ammonium molybdate and a silver salt, wherein the molar ratio of the sum of the manganese salt and the ammonium molybdate, the cobalt salt and the silver salt is 0.7:(4.9-7.35):(0.5-1.5), to obtain a second mixed system; S2, the first mixed system or the second mixed system is subjected to hydrothermal treatment at 140-150° C. to form amorphous NiCoMo doped with crystalline Ag. x Mn y The heterojunction is loaded on nickel foam to form amorphous NiCoMo doped with crystalline Ag. x Mn y Heterojunction electrode materials.
[0008] Preferably, in S1, the nickel foam is obtained according to the following process: The initial nickel foam is immersed in hydrochloric acid and subjected to ultrasonic treatment, and then washed and dried to obtain the nickel foam.
[0009] Furthermore, the ultrasonication is performed for 5-15 min.
[0010] Furthermore, the cleaning is carried out in deionized water and anhydrous ethanol in sequence, and the drying is carried out at 60-80° C. for 8-12 h.
[0011] Preferably, in S1, the cobalt salt, manganese salt and silver salt are cobalt nitrate, manganese nitrate and silver nitrate respectively.
[0012] Preferably, S1 mixes the nickel foam and the first mixed solution or the second mixed solution uniformly by ultrasonication for 5-15 min.
[0013] Preferably, in S2, the first mixed system or the second mixed system is hydrothermally treated at 140-150° C. for 2-8 h to form an amorphous NiCoMo doped with crystalline Ag. x Mn y Heterojunction electrode materials.
[0014] Preferably, S2 will be amorphous NiCoMo doped with crystalline Ag. x Mn y The heterojunction electrode material is first cleaned and then dried to complete the amorphous NiCoMo doped with crystalline Ag. x Mn y Preparation of heterojunction electrode materials.
[0015] Furthermore, the cleaning is carried out in deionized water and anhydrous ethanol in sequence, and the drying is carried out at 60-80° C. for 8-12 hours.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: Amorphous NiCoMo doped with crystalline Ag of the present invention x Mn y Heterojunction electrode material, crystalline Ag has higher conductivity, which effectively improves the conductivity and structural stability of the heterojunction material interface, thereby improving the amorphous NiCoMo x Mn y The specific capacity and cycle life of crystalline Ag doped in amorphous NiCoMo x Mn y In the process, a mixed morphology of nanorods and nanosheets is generated, forming more heterojunction interfaces, so that the electrode material has more active sites, faster ion transport channels, and a larger specific surface area, thus having better electrochemical performance. Amorphous NiCoMo x Mn y The electrode material is doped with Mo or Mo and transition metal element Mn on the basis of NiCo to further improve the electrochemical performance of NiCo. Especially in the case of Mo doping, it has better electrochemical performance and can successfully increase the charge cut-off voltage to 0.54 V at 2 mA / cm 2 The specific capacity at the current density is 9266.67 mF / cm 2 , the capacity retention rate after 1000 cycles of charge and discharge can reach more than 70%. Therefore, the heterojunction electrode material obtained by the present invention has better conductivity, specific capacity and longer cycle life when used as a supercapacitor electrode material. The Ni in the heterojunction electrode material comes from nickel foam, and the nickel foam can act as a current collector when used as a working electrode, carrying positive and negative electrode materials, and collecting and outputting the current generated by the active material during the charge and discharge process.
[0017] Amorphous NiCoMo doped with crystalline Ag x Mn y The preparation method of heterojunction electrode material adopts a one-step hydrothermal method to prepare it. The nickel foam is evenly mixed with a mixed solution containing cobalt salt, ammonium molybdate (or manganese salt) and silver salt. The nickel foam not only serves as a Ni source, but also acts as an oxidant by adjusting the hydrothermal temperature to replace crystalline Ag, and further crystalline Ag is doped into amorphous NiCoMo. x Mn y The heterojunction electrode material is formed in the process, which has simple method, controllable operation, high yield, good repetitive effect, and easy to achieve large-scale production. Ag as a crystalline material can simply and effectively improve the amorphous NiCoMo x Mn y The conductivity of the amorphous / crystalline heterojunction is higher than that of the conventional amorphous / crystalline heterojunction. The electrode material of the amorphous / crystalline heterojunction is amorphous NiCoMo x Mn y Crystalline Ag is doped inside, so there are more heterojunction interfaces, which helps to improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the target substance synthesized in Example 2 of the present invention.
[0019] Figure 2 This is a TEM image of the target substance synthesized in Example 2 of the present invention.
[0020] Figure 3 This is a constant current charge and discharge curve of the target material synthesized in Example 2 of the present invention at a voltage of 0-0.54 V.
[0021] Figure 4 The target substance synthesized in Example 2 of the present invention is 0-0.54 V voltage and 5 mA / cm 2 Cycle-capacity retention rate diagram after 1000 cycles at a current density of .
[0022] Figure 5 It is a constant current charge and discharge curve diagram of the target substance synthesized in Comparative Example 1 of the present invention at a voltage of 0-0.45 V. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection intended by the present invention.
[0024] The present invention discloses an amorphous NiCoX doped with crystalline Ag. a1 Ya2 Heterojunction electrode material, amorphous NiCoX a1 Y a2 Where X and Y are Mo and Mn.
[0025] a1 and a2 satisfy the following relationship respectively: 0<a1≤1, 0≤a2<1, a1+a2=1.
[0026] The present invention discloses an amorphous NiCoX doped with crystalline Ag. a1 Y a2 A method for preparing a heterojunction electrode material comprises the following steps: Step 1, soaking the initial nickel foam in 3 M hydrochloric acid and ultrasonically treating it in an ultrasonic machine for 5-15 min; Step 2, repeatedly washing the treated nickel foam with deionized water and anhydrous ethanol in turn, and then drying at 60-80° C. for 8-12 h; Step 3, when y=0, the dried nickel foam and the first mixed solution containing cobalt salt, ammonium molybdate and silver salt are uniformly mixed by ultrasonication in an ultrasonic machine for 5-15 min, wherein the molar ratio of the cobalt salt, ammonium molybdate and silver salt is (4.9-7.35):0.7:(0-1.5), to obtain a first mixed system; When 0<y<1, the dried nickel foam and the second mixed solution containing cobalt salt, manganese salt, ammonium molybdate and silver salt are uniformly mixed by ultrasonication in an ultrasonic machine for 5-15 min, and the molar ratio of the sum of manganese salt and ammonium molybdate, cobalt salt and silver salt is 0.7:(4.9-7.35):(0-1.5), to obtain a second mixed system; The cobalt salt, manganese salt and silver salt are cobalt nitrate, manganese nitrate and silver nitrate respectively.
[0027] Step 4, hydrothermally treating the first or second mixed system at 140-150°C for 2-8 h to obtain amorphous NiCoMo doped with crystalline Ag. x Mn y The heterojunction was loaded on the nickel foam by in-situ growth, and then washed in deionized water and anhydrous ethanol for multiple times, and then dried at 60-80 ° C for 8-12 h to obtain amorphous NiCoMo doped with crystalline Ag. x Mn y (For the convenience of description, it will be recorded as amorphous NiCoMo1 / crystalline Ag) heterojunction electrode material.
[0028] Example 1 A one-step method for preparing an amorphous NiCoMo1 electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0029] Step 2: Add the treated nickel foam to a mixed aqueous solution of ammonium molybdate and Co(NO3)2·6H2O. The amount of all salts is weighed in a certain ratio. Co(NO3)2·6H2O and (NH4)2MoO4 are 4.9 mmol and 0.7 mmol, respectively, and water is 15 mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0030] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0031] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0032] The electrochemical performance of the obtained amorphous NiCoMo1 electrode material was tested, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, the prepared electrode material as the working electrode, and 6 M KOH as the electrolyte. The Shanghai Chenhua electrochemical workstation was used to test the electrode material for cyclic voltammetry, impedance, constant current charge and discharge, and cycle performance. 2 The specific capacity at the current density is 8752.6 mF / cm 2 After 1000 cycles of charge and discharge, the capacity retention rate can reach 63.12%. Example 2: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0033] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 minutes.
[0034] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0035] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0036] The electrochemical performance of the obtained amorphous NiCoMo1 / crystalline Ag heterojunction electrode material was tested, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, the prepared electrode material as the working electrode, and 6 M KOH as the electrolyte. The Shanghai Chenhua electrochemical workstation was used to perform cyclic voltammetry, impedance, constant current charge and discharge, and cycle performance tests on the electrode material. Figure 3 The constant current charge and discharge shown in Figure 4 The cycling performance test shows that the 0-0.54 V voltage window and 2 mA / cm 2 The specific capacity at the current density is 9266.7 mF / cm 2 After 1000 cycles of charge and discharge, the capacity retention rate was 75.4%, and the coulombic efficiency remained at 99.19%. The loading amount of the electrode material on the nickel foam was 14.3 mg / cm 2 .
[0037] Example 3: A one-step method for preparing an amorphous NiCoMn1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0038] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, Mn(NO3)2·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, Mn(NO3)2·4H2O, Ag(NO3)2 are 7.35mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 15 min.
[0039] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0040] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0041] The electrochemical performance of the obtained amorphous NiCoMn1 / crystalline Ag heterojunction electrode material was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 1988.9 mF / cm at a current density of 2 .
[0042] Example 4: A one-step method for preparing amorphous NiCoMo 0.5 Mn 0.5 / The preparation method of crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 80°C for 12 h.
[0043] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O, Mn(NO3)2·4H2O and Ag(NO3)2. The amount of all salts is weighed in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4·4H2O, Mn(NO3)2·4H2O, Ag(NO3)2 are 4.9 mmol, 0.35 mmol, 0.35 mmol and 1 mmol respectively, and the amount of water is 15 mL. The solution containing nickel foam is treated with ultrasound in the dark for 10 min.
[0044] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0045] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0046] The obtained amorphous NiCoMo 0.5 Mn 0.5 / crystalline Ag heterojunction electrode material was used for electrochemical performance testing. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 7436 mF / cm at a current density of 2 .
[0047] Example 5: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 10 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0048] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 6.13mmol, 0.7mmol and 0.5mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 12 minutes.
[0049] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0050] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol for several times, and then placed in a drying oven for drying at 60°C for 10 h.
[0051] The electrochemical performance of the obtained amorphous NiCoMo1 / crystalline Ag heterojunction electrode material was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity at the current density is 8792.6 mF / cm 2 .
[0052] Example 6: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 8 h.
[0053] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1.5mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 minutes.
[0054] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 6 h.
[0055] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol for several times, and then placed in a drying oven for drying at 60°C for 10 h.
[0056] The electrochemical performance of the obtained amorphous NiCoMo1 / crystalline Ag heterojunction electrode material was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 6703.7 mF / cm at a current density of 2 .
[0057] Example 7: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 10 h.
[0058] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0059] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 2 h.
[0060] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol for several times, and then placed in a drying oven for drying at 60°C for 10 h.
[0061] The electrochemical performance of the amorphous NiCoMo1 / crystalline Ag heterojunction electrode material obtained with a hydrothermal time of 2 h was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 6153 mF / cm at a current density of 2 .
[0062] Example 8: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0063] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0064] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 140°C for 4 h.
[0065] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol for several times, and then placed in a drying oven for drying at 60°C for 8 h.
[0066] The electrochemical performance of the amorphous NiCoMo1 / crystalline Ag heterojunction electrode material obtained with a hydrothermal time of 4 h was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 8555.6 mF / cm at a current density of 2 .
[0067] Example 9: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0068] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 7.35mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0069] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 150°C for 8 h.
[0070] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0071] The electrochemical performance of the amorphous NiCoMo1 / crystalline Ag heterojunction electrode material obtained with 8 h hydrothermal time was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using the Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 10680 mF / cm at a current density of 2 .
[0072] Example 10: A one-step method for preparing an amorphous NiCoMo1 / crystalline Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0073] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0074] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 140°C for 6 h.
[0075] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0076] The electrochemical performance of the amorphous NiCoMo1 / crystalline Ag heterojunction electrode material obtained at a hydrothermal temperature of 140°C was tested. The saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode material was used as the working electrode, and 6 M KOH was used as the electrolyte. The electrode material was subjected to cyclic voltammetry, impedance, and constant current charge and discharge tests using a Shanghai Chenhua electrochemical workstation. 2 The specific capacity is 7328 mF / cm at a current density of 2 .
[0077] Comparison Example 1: A one-step method for preparing a NiCoMo1 / Ag heterojunction electrode material comprises the following steps: first step: The nickel foam was immersed in 3 M hydrochloric acid solution, deionized water and anhydrous ethanol in turn, and ultrasonicated for 5 min respectively, and then placed in a drying oven for drying at 60°C for 12 h.
[0078] Step 2: Add the treated nickel foam to a mixed aqueous solution of Co(NO3)2·6H2O, (NH4)2MoO4·4H2O and Ag(NO3)2, and weigh all the salts in a certain proportion. Co(NO3)2·6H2O, (NH4)2MoO4, Ag(NO3)2 are 4.9mmol, 0.7mmol and 1mmol respectively, and water is 15mL. The solution containing nickel foam is treated with ultrasound in the dark for 5 min.
[0079] Step 3: The ultrasonically treated nickel foam and the mixed solution were transferred to the inner lining of a stainless steel reactor and subjected to a hydrothermal reaction at 120°C for 6 h.
[0080] Step 4: After the reactor was cooled to room temperature, the nickel foam was taken out and washed with deionized water and anhydrous ethanol several times, and then placed in a drying oven for drying at 60°C for 12 h.
[0081] The electrochemical performance of the obtained NiCoMo1 / Ag heterojunction electrode material was tested, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, the prepared electrode material as the working electrode, and 6 M KOH as the electrolyte. The Shanghai Chenhua electrochemical workstation was used to perform cyclic voltammetry, impedance, and constant current charge and discharge tests on the electrode material. Figure 5 The constant current charge-discharge and cycle performance tests shown in the figure show that the voltage window of 0-0.45 V and 2 mA / cm 2 The specific capacity is 1378.8 mF / cm at a current density of 2 In addition, the loading amount of the electrode material is 0.5 mg / cm 2 .
[0082] Comparing Example 1 with Example 2, it is found that the addition of Ag element can effectively improve the electrochemical performance. This is because the added Ag changes the morphology of the entire heterojunction electrode material into a mixed structure of nanorods and nanosheets ( Figure 1 ), and crystalline Ag is doped into amorphous NiCoMo, such as Figure 2 As shown, the red area is the lattice stripes of crystalline Ag, and the blue area is the amorphous NiCoMo. It can be seen that Ag is evenly distributed between the amorphous NiCoMo. Therefore, the electrochemical performance of the electrode material is significantly improved through the synergistic effect between nanorods / nanosheets, amorphous / crystalline heterojunctions, NiCoMo and Ag multi-elements. Among them, crystalline Ag improves conductivity, while amorphous NiCoMo has a faster ion transport channel.
[0083] From the comparison between Example 2 and Comparative Example 1, it can be seen that increasing the hydrothermal temperature will generate an amorphous NiCoMo1 / crystalline Ag heterojunction, thereby making the electrode material have a higher capacity and voltage window.
[0084] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. Amorphous NiCoMo doped with crystalline Ag x Mn y A heterojunction electrode material, characterized in that The heterojunction electrode material is composed of amorphous NiCoMo x Mn y and crystalline Ag, wherein crystalline Ag is doped in amorphous NiCoMo x Mn y In the amorphous NiCoMo x Mn y The x and y in the equation satisfy the following formula: 0<x≤1, 0≤y<1, x+y=1.
2. Amorphous NiCoMo doped with crystalline Ag as claimed in claim 1 x Mn y A method for preparing a heterojunction electrode material, characterized in that: The following steps are involved: S1, when y=0, uniformly mixing the nickel foam with a first mixed solution containing a cobalt salt, ammonium molybdate and a silver salt, wherein the molar ratio of the cobalt salt, the ammonium molybdate and the silver salt is (4.9-7.35):0.7:(0.5-1.5), to obtain a first mixed system; When 0<y<1, the nickel foam is evenly mixed with a second mixed solution containing a cobalt salt, a manganese salt, ammonium molybdate and a silver salt, wherein the molar ratio of the sum of the manganese salt and the ammonium molybdate, the cobalt salt and the silver salt is 0.7:(4.9-7.35):(0.5-1.5), to obtain a second mixed system; S2, the first mixed system or the second mixed system is subjected to hydrothermal treatment at 140-150° C. to form amorphous NiCoMo doped with crystalline Ag. x Mn y The heterojunction is loaded on nickel foam to form amorphous NiCoMo doped with crystalline Ag. x Mn y Heterojunction electrode materials.
3. The amorphous NiCoMo doped with crystalline Ag according to claim 2 x Mn y A method for preparing a heterojunction electrode material, characterized in that: In S1, the nickel foam is obtained according to the following process: The initial nickel foam is immersed in hydrochloric acid and subjected to ultrasonic treatment, and then washed and dried to obtain the nickel foam.
4. The amorphous NiCoMo doped with crystalline Ag according to claim 3 x Mn y A method for preparing a heterojunction electrode material, characterized in that: The ultrasonication is performed for 5-15 min.
5. The amorphous NiCoMo doped with crystalline Ag according to claim 3 x Mn y A method for preparing a heterojunction electrode material, characterized in that: The cleaning is carried out in deionized water and anhydrous ethanol in sequence, and the drying is carried out at 60-80° C. for 8-12 h.
6. The amorphous NiCoMo doped with crystalline Ag according to claim 2 x Mn y A method for preparing a heterojunction electrode material, characterized in that: In S1, the cobalt salt, manganese salt and silver salt are cobalt nitrate, manganese nitrate and silver nitrate respectively.
7. The amorphous NiCoMo doped with crystalline Ag according to claim 2 x Mn y A method for preparing a heterojunction electrode material, characterized in that: S1 uniformly mixes the nickel foam with the first mixed solution or the second mixed solution by ultrasonication for 5-15 min.
8. The amorphous NiCoMo doped with crystalline Ag according to claim 2 x Mn y A method for preparing a heterojunction electrode material, characterized in that: In S2, the first mixed system or the second mixed system is hydrothermally treated at 140-150°C for 2-8 h to form an amorphous NiCoMo doped with crystalline Ag. x Mn y Heterojunction electrode materials.
9. The amorphous NiCoMo doped with crystalline Ag according to claim 2 x Mn y A method for preparing a heterojunction electrode material, characterized in that: S2 will be doped with crystalline Ag amorphous NiCoMo x Mn y The heterojunction electrode material is first cleaned and then dried to complete the amorphous NiCoMo doped with crystalline Ag. x Mn y Preparation of heterojunction electrode materials.
10. The amorphous NiCoMo doped with crystalline Ag according to claim 9 x Mn y A method for preparing a heterojunction electrode material, characterized in that: The cleaning is carried out in deionized water and anhydrous ethanol in sequence, and the drying is carried out at 60-80° C. for 8-12 h.
Citation Information
Patent Citations
A method for preparing crystalline-amorphous MoO3@Ni3S2 materials for supercapacitors
CN111540609B
Nickel oxalate composite amorphous nickel cobalt boride supercapacitor electrode material and preparation method and application thereof
CN117457401A
Cited By
Negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN119601645A
Negative electrode material, preparation method thereof, negative electrode sheet and sodium ion battery
CN119601645B